Análises ontogenéticas do pericarpo de espécies deMimosa Linnaeus (Fabaceae, Mimosoideae) - Oliveira, Jonathas Henrique Georg De; Iwazaki, Maísa Carvalho [UNESP]; Oliveira, Denise Maria Trombert (Instituto de Botânica, 2014)
The objectives were to analyze ontogenetically the fruits of Mimosadaleoides, M. dolens var. anisitsii and M.orthacantha, comparing themselves and identifying them correctly. Collections were made in Botucatu, São Paulo State, Brazil, and the fruits in several development stages were prepared according to usual anatomical techniques. During pericarp development, dendritics and spine-like emergences are produced, and an adaxial meristem is installed, originating the multiseriate lignified outer endocarp and the uniseriate parenchymatous inner endocarp. The structure of pericarp follows the pattern for Fabaceae, with uniseriate exocarp, parenchymatous and vascularized mesocarp, and heterogeneous endocarp. In M. daleoides and M.orthacantha, false septa are formed where transverse fragmentation of the pericarp occur; moreover, lignified tissue is produced externally to the ventral and dorsal bundles. Therefore, the fruits of these two species are craspedium andM. dolens var. anisitsii produces legumes with passive dehiscence.

Os objetivos foram analisar ontogeneticamente frutos de Mimosadaleoides, M. dolens var. anisitsii eM. orthacantha, comparálos e classificá-los corretamente. Coletas realizadas em Botucatu, SP, Brasil, renderam frutos nos vários estádios de desenvolvimento, preparados segundo técnicas anatômicas usuais. Durante o desenvolvimento do pericarpo, emergências dendríticas e espiniformes são formadas, e um meristema adaxial é instalado, originando o endocarpo externo, multisseriado e lignificado na maturidade, e o interno, unisseriado e parenquimático. A estrutura do pericarpo segue o padrão para as Fabaceae, com exocarpo unisseriado, mesocarpo parenquimático e vascularizado, e endocarpo heterogêneo. Em M.daleoides e M. orthacantha, formam-se falsos septos, onde o pericarpo fragmenta-se transversalmente; além disso, tecido lignificado forma-se externamente aos feixes ventrais e ao dorsal. Os frutos destas duas espécies são, portanto, craspédios e Mimosa dolens var.anisitsii forma legumes com deiscência passiva.
Ontogenetic analysis of the pericarp of species of Mimosa Linnaeus (Fabaceae, Mimosoideae)
Keywords: anatomy; fruit; Mimosa; morphology; ontogenesis; anatomia; fruto; Mimosa; morfologia; ontogênese